Issues and solutions on inventive problems-solving skills (IPSS) in invention course - Tee Tze Kiong; Nuraliah Abd Nasir; Nurulwahida Azid; Mimi Mohaffyza Mohamad; Wu Ming Chang; Charanjit Kaur Swaran Singh (Jurnal Cakrawala Pendidikan, 2022)
Problem solving skills are the ability to solve problems in an effective way without any impediments. The purpose of this study is to identify the importance and issues on root cause identification for the problem among students and teachers of Invention’s course. This research applied mixed-method comprising quantitative and qualitative approaches. A total of 133 students and 30 teachers of Invention were involved in the survey at the secondary school in Johor. A survey questionnaire and semi-structured interviews were applied in this research. The results of t-test revealed that there was no significant difference on the importance [t (133) = -2.915; p = .194, (p .05)] and issues [t (133) = .142; p = .09, (p .05)] for gender. Next, two-way ANOVA test showed that the level of importance (F (30) = 2.874, p = .061) and issues (F (30) = 6.846, p = .112) of the skills did not depends on the gender of the teacher and teaching experiences. Majority teachers support the application of the Theory of Inventive Problem-Solving Skills using Function Analysis for root cause identification (TRIZ). Thus, the development of self-learning module is proposed as teaching material to facilitate the application of the skills for the Invention course.